A Survey Review and Current Status of Risk Assessment and Management and its Inputs in the Australian Minerals Industry (The Australasian Institute of Mining and Metallurgy, 2003)
This paper provides an insight into the current status of risk management practices within our industry, based on an industry wide survey, with deliberate cross-reference to quantitative analysis. This survey showed that quantitative assessments appear to be mainly hampered only by the lack of reliable data and industry expertise to carry out such assessments. A short case study will illustrate some of the necessary basic tools and data types that would enable the industry to tap into an additional range of business improvement dimensions to more effectively manage the diverse and changing risk profile of the mining sector.